2022
DOI: 10.1002/jor.25303
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional reconstruction of Kambin's triangle based on automated magnetic resonance image segmentation

Abstract: The three‐dimensional (3D) anatomy of Kambin's triangle is crucial for surgical planning in minimally invasive spine surgery via the transforaminal approach. Few pieces of research have, however, used image segmentation to explore the 3D reconstruction of Kambin's triangle. This study aimed to develop a new method of 3D reconstruction of Kambin's triangle based on automated magnetic resonance image (MRI) segmentation of the lumbar spinal structures. An experienced (>5 years) “ground truth” spinal pain physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Unfortunately, many other segmentation studies aiming at recreating lumbar structures focused on bones [20][21][22], discs [23], and spinal muscles [19]. To the authors' knowledge, only one study succeeded in recreating a comprehensive 3D model of the Kambin's triangle including bones, dura mater, discs, and nerve roots [16]. In their study, Su et…”
Section: Review Kambin's Triangle Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, many other segmentation studies aiming at recreating lumbar structures focused on bones [20][21][22], discs [23], and spinal muscles [19]. To the authors' knowledge, only one study succeeded in recreating a comprehensive 3D model of the Kambin's triangle including bones, dura mater, discs, and nerve roots [16]. In their study, Su et…”
Section: Review Kambin's Triangle Reconstructionmentioning
confidence: 99%
“…Although it is well agreed that a thorough understanding of foraminal anatomy (including Kambin's triangle) is important for the success of t-MISS, fewer studies have been successful at reconstructing a three-dimensional (3D) image of the Kambin's triangle [12,14,15]. This 3D reconstruction is important for surgical planning and real-time navigation in the t-MISS operating field [16]. Here, we present the most up-to-date review on the 3D reconstruction of Kambin's triangle, and a preview of the current and next era of spinal surgical management through the triangle.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies 19,20 have focused on the automatic segmentation of the vertebral notch and articular processes, essential to lumbar structures. Su et al 20 . have developed a method for 3D reconstruction of Kambin's triangle, not for rapid 3D LIVF reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Previous studies have demonstrated the success of deep learning in the automatic MRI segmentation, but these studies have mainly focused on segmenting vertebra bodies and intervertebral discs without segmenting the vertebral notch and articular processes. 17,18 Few studies 19,20 have focused on the automatic segmentation of the vertebral notch and articular processes, essential to lumbar structures. Su et al 20 have developed a method for 3D reconstruction of Kambin's triangle, not for rapid 3D LIVF reconstruction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation